Surfactant Protein D as a Potential Biomarker and Therapeutic Target in Ovarian Cancer - Kumar, Juhi; Murugaiah, Valamarthy; Sotiriadis, Georgios; Kaur, Anuvinder; Jeyaneethi, Jeyarooban; Sturniolo, Isotta; Alhamlan, Fatimah S.; Chatterjee, Jayanta; Hall, Marcia; Kishore, Uday; Karteris, Emmanouil (Frontiers in Oncology, 2019)
Surfactant protein D (SP-D) is an important innate immune molecule that is involved in clearing pathogens and regulating inflammation at pulmonary as well as extra-pulmonary sites. Recent studies have established the role of SP-D as an innate immune surveillance molecule against lung and pancreatic cancer, but little is known about its involvement in signalling pathways it can potentially activate in ovarian cancer. We focused our study to on ovarian cancer by performing bioinformatics analysis (Oncomine) of datasets and survival analysis (Kaplan-Meier plotter), followed by immunohistochemistry using ovarian cancer tissue microarrays. SP-D mRNA was found to be expressed widely in different types of ovarian cancer irrespective of stage or grade. These in silico data were further validated by immunohistochemistry on clinical tissues. High transcriptional levels of SP-D were associated with unfavorable prognosis (overall and progression-free survival). We also detected SP-D protein in Circulating Tumour Cells of 3 ovarian cancer patients, suggesting that SP-D can also be used as a potential biomarker. Previous studies have shown that a recombinant fragment of human SP-D (rfhSP-D) induced apoptosis in pancreatic cancer cells via a Fas-mediated pathway. In this study, we report that treatment of SKOV3 cells (an ovarian cancer cell line) with rfhSP-D led to a decrease in cell motility and cell proliferation. This was followed by an inhibition of the mTOR pathway activity, increase in caspase 3 cleavage and induction of pro-apoptotic genes Fas and TNF-α. These data, suggesting a likely protective role of rfhSP-D against ovarian cancer, together with the observation that the ovarian cancer microenvironment overexperesses SP-D leading to poor prognosis, seems to suggest that the tumour microenvironment components manipulate the protective effect of SP-D in vivo.